« J’étais hyper-endetté, il fallait que je bosse » - Arnaud Mias (La Nouvelle Revue du Travail)
This material presents large excerpts from an interview conducted in Paris in March 2017 with Nathan, an administrative agent of the French Ministry of Education who is working as a cycle courier for a digital meal delivery platform. This article draws a portrait of a profile of platform workers: neither students finding it a relatively easy way to obtain an income considered correct, nor pseudo-independent aspiring to salary status, Nathan’s case is that of a bi-activity, which exacerbates the logic of cumulation of occupations allowed by the status of microentrepreneur. By its uniqueness, this case sheds light on certain aspects of these young men’s involvement in the urban delivery and highlights the ambivalence of a situation taken to its extreme, juxtaposing a clear-sighted and critical discourse on working and employment conditions with a commitment that is at once important, determined and relatively lasting in the service of the platform.